Fast pyrolysis of macadamia nutshell in an auger reactor: Process optimization using response surface methodology (RSM) and oil characterization. (1st February 2023) - Hasan, M.M.; Rasul, M.G.; Jahirul, M.I.; Khan, M.M.K.
Highlights: Macadamia Nutshell fast pyrolysis optimization using response surface methodology. The bio-oil yield of 43.37 wt% was found at optimum operating condition. The variation between the experimental and predicted yield of bio-oil was 2.75%. Analysis of oil using GC–MS showed the presence of 11 chemical functional groups. The higher viscosity and water content limit oil's application as engine fuel. Abstract: The aim of this study is to optimize a fast pyrolysis process to produce maximum yield of pyrolysis oil using macadamia nutshell (MNS) as feedstock. The fast pyrolysis process was carried out in an auger reactor. The process was optimized by response surface methodology (RSM) coupled with Box-Behnken design (BBD) considering temperature, residence time and feedstock particle size as independent variables and bio-oil yield as response. The maximum bio-oil yield (43.37 wt%) was obtained at a temperature of 471.21 °C, residence time of 141.82 sec, and feedstock particle size of 3.78 mm. Analysis of variance (ANOVA) confirms that the fast pyrolysis of MNS for maximum bio-oil yield highly depends on temperature followed by feedstock particle size and residence time, respectively. Analysis of the bio-oil obtained at optimum condition shows the presence of 11 functional groups, with the phenol, aromatics and alcohol groups dominating the others. The physicochemical properties analysis reveals that the obtained bio-oil has higher viscosity (11.51 Cst) and water content (20.4 %) which makes it unsuitable for engine application. However, the produced bio-oil can be used as fuel in other applications such as in boilers and as additives to produce valuable chemicals.